Role of serum cystatin C in the prediction of acute kidney injury following pediatric cardiac surgeries: A single center experience. Issue 49 (9th December 2022) - Zakaria, Marwa; Hassan, Tamer; Refaat, Ali; Fathy, Manar; Hashem, Mustafa I.A.; Khalifa, Naglaa; Ali, Ahmed A.; Elhewala, Ahmed; Ramadan, Ahmed; Nafea, Alaa
Abstract : Intense contemporary research is directed towards validating novel biomarkers to predict acute kidney injury (AKI) in children undergoing cardiothoracic surgeries. We aimed to evaluate the role of cystatin C in early prediction of AKI following cardiac surgery in children with congenital heart disease. Prospective observational cohort study was conducted on 40 children with congenital heart disease undergoing cardiac surgery. 40 healthy children with matched age and sex were enrolled as a control group. Children were subjected to physical examination, routine blood tests, echocardiography, and measurement of plasma cystatin C level on different occasions. The median age of the patients was 3.65 years, a range from 1 to 5 years with no significant difference regarding the age and sex of cases and control groups. The mean serum cystatin C level in patients was 0.75 ± 0.15, 1.35 ± 0.34 and 1.21 ± 0.38 mg/dL (preoperative, at 6 h and at 24 h postoperative, respectively) with statistically significant difference P  < .05. 30% of the patients developed postoperative AKI with significantly higher serum cystatin C at 6 hours postoperative >1.33 mg/dL compared to preoperative level p P  < .05. Serum cystatin C level was positively correlated with cardiac bypass time, ischemic time and length of hospital stay at 6 hours postoperative. Serum cystatin C is a sensitive marker for early detection of AKI following cardiac surgery in children with congenital heart disease and it was positively correlated with cardiac bypass time, ischemic time and length of hospital stay.